Crossword Puzzle Increase Attention of Children with ADHD - Ah. Yusuf; Khoridatul Bahiyah; IGA Wadmi (Jurnal Ners, 2009)
Introduction: Attention deficit is one of three main problems of children with Attention Deficit Hyperactivity Disorder (ADHD). Children experience difficulty of paying attention and concentrating to one or more things or objects. As a results these children cannot perform the task well. Crossword puzzle is one of games that may increase attention and concentration. The aim of this study was to analyze the effect of crossword puzzle to increase attention of children with ADHD. Method: Pre-experimental design was employed in this study. The population was ADHD students in Cakra Autisme Therapy. Seven students were recruited by means of purposive sampling. The independent variable was crossword puzzle and the dependent variable was the increase of attention. Data were collected using observation sheet and analyzed using Wilcoxon Signed Rank Test with level of significance of α≤ 0.05. Result: Result showed that crossword puzzle could increase attention. Respondent’s attention improved from less to good attention, particularly in playing activities (p=0.014).This finding suggests that there was differences of attention between pre and post-test. It can be concluded that crossword puzzle can increase attention of the students with ADHD.Discussion: It is recommended for teachers and parents of ADHD children to give them crossword puzzle game everyday at school or at home. Further studies should involve larger sample size and employs another game not only to increase attention, but also reduce hyperactivity and impulsivity of ADHD child.